PENERAPAN ALGORITMA GENETIKA MENGGUNAKAN METODE SELEKSI ROULETTE WHEEL PADA OPTIMASI PENENTUAN KOMPOSISI BAHAN PAKAN AYAM BROILER - Iqbal Fairus Zamani; Galih Wasis Wicaksono; Agus Eko Minarno (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2018)
Along with many various human activity to fulfill the food nutritional in take vegetable nutrition and animal nutrition must be fulfilled. Animal nutrition is a needs that aften consumed by many people and one of those is broiler chicken. Broiler chicken is a livestuck chicken that easily produce, so there are so many broiler chicken farm that we could see in many place. But there are some problem that occur in most broiler breeders such as the composition of food ingredients and high ration costs. To fulfill the right composition of ingredients with minimum cost, researchers offer a solution by using genetic algorithm in deter mining the composition of broiler food ingredients. This aplication uses 50 ingredients of broiler chicken livestock along with nutrition. This study used roulette wheel methods. The result of this study obtained optimum parameters with population size of 400, various generation of 350 and pc 0.1 and pm 0.8 combinations of 10 times test. This result is a composition of broiler food ingredients that meet the nutritional needs with minimal cost.